A Benchmark on the Alternative Education System for Engineering Courses - Borreo, Raiza Dimapilis (JPAIR Institutional Research, 2016)
Offered by the Commission on Higher Education (CHED) under the Republic of the Philippines, the Expanded Tertiary Education Equivalency and Accreditation (ETEEAP) is an alternative method of earning a college degree. There are 96 Higher Education Institutions (HEIs) that offer ETEEAP in the country, 21 of which offer engineering programs. The study aimed to obtain the best practices being implemented by deputized HEIs offering college degree programs under ETEEAP, particularly, in the field of engineering and check its correlation to the number of graduates. Visitations, observations, and interviews were performed in two selected universities. Information about the enrolled and graduated students were collected. Data gathered were analyzed and tabulated. As an analysis, the policies of the two universities are in accordance of the CHED and, therefore, are similar. A significant increase in the number of engineering graduates under ETEEAP has been recorded. However, some students were not able to finish a program on time. The results of the study can be used as a guiding tool for schools aiming to offer ETEEAP or a reference for continuous improvement of the ETEEAP programs in sustaining the educational needs of the student-clienteles.
Keywords: Engineering Education; ETEEAP; tertiary; alternative; descriptive design; Philippines